Strategi Kreatif Penulis dalam Menjaga Brand Image PT. Highend Multimedia Indonesia - Azza, Aulia; Pranata, Rici Tri Harpin; Marithasari, Harries (Jurnal Dinamika Ilmu Komunikasi, 2025)
This study thoroughly analyzes the implementation of creative strategies carried out by PT. Highend Multimedia Indonesia to maintain its brand image. The main focus is on the use of exclusivity and authority as pillars of branding. This research uses mix methods, in which researchers were actively involved during a four-month internship. The results show that the writing strategy based on Positioning Theory proved to be very effective in increasing reader engagement. This success was validated by the achievement of an article titled “When $1,000 Bag Charms Become the Latest Small Luxury in the Retail World”. The article broke into the Top 3 Viewa in terms of views in August 2025, strongly reinforcing the brand's position as a credible and authoritative source of information in its industry. The main conclusion of this study is that consistency in positioning is an absolute strategic key. To maintain and enhance this authority, investing in premium research tools is highly recommended. This consistency and research support will ensure PT. Highend Multimedia Indonesia continues to excel in its exclusive narrative.